The Meaning of Socio Cultural Values From the Islamic Law Perspective - Bahari, Raha; Sivana, Ezmi (MILRev: Metro Islamic Law Review, 2022)
This study aims to discuss the meaning of social and cultural values ​​from the perspective of Islamic legal philosophy or Islamic law itself. In our country, Indonesia has very high socio-cultural values, where the culture found in Indonesia is very diverse. And apart from that, social factors arising from various cultures must be related or in harmony with Islamic law for Muslims. And also has the factor of mutual respect for religious communities. This research is a literature study with the data collection technique being documentation. An important finding in this research is that Islamic law will be able to change social society, if Islamic law is obeyed and implemented and becomes a guide, and even becomes a custom for society. Apart from that, Islamic law can change social society if Islamic law is absorbed into positive law for a country.